HUBUNGAN LAMA PEMAKAIAN KONTRASEPSI SUNTIK KB 3 BULAN DENGAN PENINGKATAN BERAT BADAN PADA AKSEPTOR KB DI KLINIK AULIA JOMBANG - Setiyawati, Ita; Mudrikatin, Siti; Rina Mardiana, Heppy (LPPM STIKES HUSADA JOMBANG, 2023)
According to the National Population and Family Planning Agency (BKKBN) of East Java Province, the most widely chosen type of contraception is injection contraception, which is 68.10%. Meanwhile, in September 2019 the most injections were used (50.51%), followed by pills (18.61%), IUDs (11.97%), implants (11.77%), MOW (4.77%), condoms ( 1.97%) and MOP (0.40%). The most widely used injectable contraceptive is the Depo Medroxy Progesterone Acetate (DMPA) injectable contraceptive. Weight gain is one of the side effects that DMPA injection contraceptive acceptors often complain about. This research method is observational analytic using secondary data. While the analysis technique used is Spearman Rank correlation analysis. The results showed that there was a relationship between the duration of using injectable contraceptives for 3 months and the increase in body weight of the acceptors. The conclusion of this study is that there is a relationship between duration of use of DMPA injectable contraceptives and changes in body weight at Aulia Clinic Jombang with p = 0.002.